Sosialisasi Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM di Desa Pelawan - Adi Bhakti; Nyimas Dian Maisyarah; Al Parok; Zulgani Zulgani; Hardiani Hardiani (WIDA Publishing, 2022)
This service activity is in the form of socializing the preparation of SME financial reports based on SAK EMKM. The activity was carried out in Pelawan Village, Kecamatan Pelawan, Sarolangun Regency. This service aims to provide knowledge to SME business actors how to prepare proper & good financial reports, in accordance with applicable regulations so that it can make it easier to evaluate the businesses’ financial performance. This service activity uses the lecture method, discussion, audio-visual media, and the practice of preparing financial reports. The activity plan to be carried out is to prepare SME Financial Reports based on SAK EMKM for SME actors in Pelawan Village, Kecamatan Pelawan, Sarolangun Regency, Jambi Province.